Peningkatan Kemampuan Literasi Qur’ani Anak Usia Dini melalui Metode Iqra di RA Al-Ikhlash - Nabila, Alfika; Almeera Irawan, Gusthine; Anis, Nur (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
The skill of readings the Qur'an one of the fundamental aspect of Islamic education, particularly from an early age. During early developmental stages, children require an engaging, systematic approach tailored to their characteristics to effectively recognize and reads the Qur’an. The Iqra methods is widely used to introduce Arabic letters gradually through six structured levels. This study aims to examine the implementation of the Iqra method in Qur’anic reading instruction at RA Al-Ikhlash in Tasikmalaya and to identify the challenges and solutions encountered in its application. The research adopted a qualitative approach, and data were collected using techniques including observation, interviews, and documentation. The findings reveal that the Iqra method is implemented in stages according to each volume, using both individual and combined classical-individual approaches based on the child’s reading ability. The learning process is also enriched by instilling moral values through Islamic storytelling. Challenges include low concentration among students, limited parental involvement, and the lack of digital learning media. In response, teachers adopt creative, patient approaches and foster strong communication with parents. Evaluation is conducted by teachers from other classes to ensure objectivity. This study recommends strengthening the collaboration between educators and parents, as well as developing engaging educational media to support effective Qur’anic reading instruction for young children. The novelty of this study lies in the integration of moral values through Islamic storytelling within the Iqra method, combined with cross-class teacher evaluations as an effective strategy to enhance Qur’anic literacy among early childhood learners